Education in Sexuality and Equality: Needs in the Initial Training of Teachers in Spain - María Teresa Bejarano-Franco; Irene Martínez-Martín; Montserrat Blanco-García (Universidad Nacional, Costa Rica, 2022)
Introduction. Sexuality and equality education are considered areas of relevant pedagogical research and intervention within current educational contexts in view of the violence and inequalities derived from the patriarchal system. Aims. This paper presents the main results of a research study that seeks to analyze the competence in sexuality and equality of university students during teacher training in Spain (Castilla la Mancha University). Method. For this, the study used a quantitative methodology and administered a nine-dimension questionnaire to 371 students. Results. The study revealed the weak acquisition of competence in sexuality and equality and the persistence of stereotyped images of sexualities. Furthermore, these findings show that future teachers have a weak equality-based professional practice due to an educational approach that lacks a gender perspective. Conclusions. The main conclusions highlight the evident formative needs in sexuality and equality and the absence of transforming feminist knowledge. All this can affect the development of quality education in sexuality and equality in students' future educational practices.